PEMAHAMAN KARYAWAN TERHADAP VISI, MISI DAN TUJUAN FIKOM UPDM (B) - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The role of the vision and mission of an organization in both the fields of education, business and government is crucial in an effort to achieve success, relates that every organization must have the vision and mission of the philosophy as a guide for the present and future. Vision is a picture (insight) or a statement of what the organization wants to be realized in the present and the future. While the mission statement is implemented by considering the formulation of the assertion and desire as well as giving a clear direction.Â This study aims to determine the vision and mission of understanding employee FIKOM UPDM (B) as a basis in carrying out their daily work.Â The results showed that the research results, it can be described many of the employees who do not understand the meaning of the vision and mission FIKOM UPDM (B), and it showed when they carry out the work, such is not the lack of referrals or direct supervisor to a subordinate to do with vision and mission in accordance with work responsibilities; does not work in accordance with the organization and work or description of existing jobs; outside office during working hours; individual products is not clear; synergy between employees in the morning and afternoon never happened, etc.